2004
DOI: 10.1039/b314814a
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of a di-N-heterocyclic carbene-amido complex of palladium(ii)

Abstract: A diimidazolium salt incorporating a secondary amine moiety has been used to prepare a palladium(II) di-N-heterocyclic carbene amino complex that can be deprotonated with NaH to give the first example of a transition metal NHC-amide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 22 publications
4
65
0
1
Order By: Relevance
“…The imidazolium moieties adopt a transoid arrangement with respect to one another with the Pd-C(NHC) bond length being 1.948(2) Å, which is relatively short when compared to chelating bis-NHC complexes. [14,19,35,36] The Pd-C(NHC) bond length is, however, comparable to those in which the palladium(II) centre possesses only one NHC donor. [37,38] The shortest intermolecular contacts in the structure are CH···Cl interactions involving the acetonitrile solvent molecules, aryl rings and methylene groups, with the H···Cl distances in the region of 2.9 Å. Metal-coordinated chloride is known to be a good hydrogen-bond acceptor.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The imidazolium moieties adopt a transoid arrangement with respect to one another with the Pd-C(NHC) bond length being 1.948(2) Å, which is relatively short when compared to chelating bis-NHC complexes. [14,19,35,36] The Pd-C(NHC) bond length is, however, comparable to those in which the palladium(II) centre possesses only one NHC donor. [37,38] The shortest intermolecular contacts in the structure are CH···Cl interactions involving the acetonitrile solvent molecules, aryl rings and methylene groups, with the H···Cl distances in the region of 2.9 Å. Metal-coordinated chloride is known to be a good hydrogen-bond acceptor.…”
Section: Resultsmentioning
confidence: 97%
“…[8] Furthermore, palladium complexes of the type Pd(pyridine)Cl 2 (NHC) and PdCl 2 (NHC) 2 have been found to exhibit potent anticancer activity. [9] Various bis-NHC ligands have been reported, which are usually linked by alkenic chains [7,[10][11][12][13] or an N-donor such as a pyridyl derivative or amine, [14][15][16] and tend to form chelating complexes with metals. NHC ligands containing a xylylene-bridge are surprisingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Douthwaite et al have shown that this is a viable route to the complex A. 36 However, treating our more rigid proligands 3a or 3b with Ag 2 O in DCM at room temperature gave an intractable mixture of products. Performing the reaction in refluxing THF also gave an unidentifiable mixture, as did including Pd(OAc) 2 could not be isolated.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] Most closely related to this work, Douthwaite has described the palladium [CNC] complex A and, during the course of our research, Luo has reported the Pd complexes (B). 36,37 Fig . 1 The synthesis of the amine bis(imidazolium) pro-ligands proceeded with a palladium catalysed amination of 2-bromoiodobenzene to give bis(2-bromophenyl)amine (1) using a procedure adapted from the literature (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Ag(I) complexes of more flexible bis-NHC ligands bearing linkages incorporating amino/amido [8], and ether [9] functionalities have been reported, the latter structurally characterised and found to be dinuclear [10], as well as ligands with chiral linker groups [11]. .2BF 4 We were motivated to produce potentially tridentate functionalised bis-NHC ligands for Pd(II) with similar geometries to I but with the pyridine donor replaced by weaker furan and thiophene moieties, and report here some examples of Ag(I) complexes of these ligands.…”
Section: Introductionmentioning
confidence: 99%